Research on Profit Allocation of Agricultural Products Co-Delivery Based on Modified Interval Shapley Value - Wang, Chenglin; Zhou, Zhicheng; Yu, Xiaohui; Chen, Jintao; Li, Pengnan; Wang, Ziqi (Sustainability, 2023)
Most of the domestic wholesale markets have many operating entities, and the level of organization and scale is not high; therefore, at this stage, building a shared business platform and carrying out common distribution is an important way to improve the overall efficiency of the wholesale market distribution operations and the level of the intensive utilization of key resources such as vehicles. Carrying out common distribution requires the formation of a good synergy mechanism among the participating subjects, in which the design of a scientific and reasonable benefit distribution scheme, especially in balancing the relationship between government resources and social resources, is particularly important. As the benefit distribution of cooperation is affected by the dynamic changes of the resource input ratio, the distribution operation scale, the risk taking, and other factors, this paper establishes a multi-weight interval Shapley value method benefit distribution model, which reflects the effect of the key parameter variables. Through the empirical analysis of Beijing’s wholesale markets for agricultural products, the results show that the revised benefit distribution is more in line with the interest demands among multiple subjects and is positively correlated with the contribution degree among the participating subjects, which can better mobilize the cooperation enthusiasm of the participating enterprises and provide a new methodological path to solve the problem of common distribution in wholesale markets. The distribution model constructed in this paper further enriches the relevant research content in the field of common distribution and is of reference value for the benefit distribution problem that requires comprehensive consideration of the dynamic change in the multiple parameters affecting the relationship.